STRATEGI TATA KELOLA KOLABORATIF DIGITAL DALAM PENGEMBANGAN USAHA KULINER DI KOTA LHOKSEUMAWE - Sari, Tiara Puspita; Aisyah, Ti; Alfiady, Teuku (FISIP Universitas Malikussaleh, 2025)
Collaborative governance is a governance model that involves various stakeholders - government, private sector, and community - in joint decision-making. Digitalization is an urgent need for culinary MSMEs in Lhokseumawe City to increase competitiveness and market access. This study aims to analyze the implementation of collaborative governance in supporting the digital transformation of culinary MSMEs and identify the obstacles faced. The study used a qualitative approach with observation, interview, and documentation techniques. Data analysis was carried out through data reduction, data presentation, and drawing conclusions. The Ansell and Gash collaborative governance model was used in the face-to-face dialogue collaboration process, building trust, commitment to the process, sharing understanding and interim results. The results of the study showed that digital literacy was still low, limited access to technology and capital, and coordination was not optimal between stakeholders. However, collaboration between the Industry, Trade, and Cooperatives Office with MSME associations and the private sector has begun to develop. It is recommended that more targeted policies and support for access to technology and finance be strengthened to accelerate the digitalization of culinary MSMEs in Lhokseumawe.